IMPLEMENTASI TEORI HUMANISTIK DALAM MEMBENTUK KARAKTER TANGGUNG JAWAB PESERTA DIDIK DI SMP NEGERI 57 HALMAHERA SELATAN - Muhammad, Syahril; Hasmawati, Hasmawati; Wahab, Mufita (Jurnal GeoCivic, 2023)
The research background analyzes the implementation of humanistic theory in forming the character of student responsibilities in schools. The implementation of learning activities certainly does not immediately start teaching and learning activities, but teachers and students must pay attention to class cleanliness so that students will get used to having a responsible attitude towards the environment and surroundings and after it initiates the learning process, the research objectives are (1). Knowing how to implement humanistic theory in shaping the character of the responsibilities of students at SMP Negeri 57 Halmahera Selatan, (2). Knowing what factors influence the implementation of humanistic theory in shaping the character of the responsibilities of students at SMP Negeri 57 Halmahera Selatan. Research method The research method used is descriptive qualitative research with the case study method, the location of this research was conducted at SMP Negeri 57 Halmahera Selatan .Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â  Based on the research results it can be concluded that: (1). For teachers, the results of this study can be a basis for teachers in optimizing the implementation of humanistic theory in shaping the character of students' responsibilities at SMP Negeri 57 Halmahera Selatan. (2). For schools, it is hoped that they can evaluate the implementation of humanistic theory in shaping the character of the responsibilities of students at SMP Negeri 57 Halmahera Selatan, in teaching and learning activities so that they run optimally. (3). For future researchers, this research can be explored further and adapted to the context of the schools studied to develop the implementation of humanistic theory in shaping the character of students' responsibilities at SMP Negeri 57 Halmahera Selatan.Ã‚Â